2014
DOI: 10.5194/acp-14-11475-2014
|View full text |Cite
|
Sign up to set email alerts
|

Simulating black carbon and dust and their radiative forcing in seasonal snow: a case study over North China with field campaign measurements

Abstract: Abstract.A state-of-the-art regional model, the Weather Research and Forecasting (WRF) model (Skamarock et al., 2008) coupled with a chemistry component (Chem) (Grell et al., 2005), is coupled with the snow, ice, and aerosol radiative (SNICAR) model that includes the most sophisticated representation of snow metamorphism processes available for climate study. The coupled model is used to simulate black carbon (BC) and dust concentrations and their radiative forcing in seasonal snow over North China in January-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 83 publications
(170 reference statements)
8
113
0
1
Order By: Relevance
“…Chýlek et al, 1983;Warren, 1984;Clarke and Noone, 1985;Warren and Clarke, 1990;Grenfell et al, 2002;Lee Taylor and Madronich, 2002;Jacobson, 2004;Flanner et al, 2007;Doherty et al, 2010;Reay et al, 2012;Ye et al, 2012;King, 2013, 2014). Field observations and modelling simulations have also shown that increases in dust deposition to snow lead to radiative forcing that affects the energy balance of snow (Woo and Dubreuil, 1985;Aoki et al, 1998;Painter et al, 2007Painter et al, , 2012Huang et al, 2011;Wang et al, 2013;Zhang et al, 2013;Zhao et al, 2014;Yasunari et al, 2014). However, although anthropogenic deposits in polar snow and ice have been well characterised, studies on the effects of natural mineral aerosol deposits are more scarce.…”
Section: L Lamare Et Al: Mineral Aerosol Deposits On Sea Icementioning
confidence: 99%
“…Chýlek et al, 1983;Warren, 1984;Clarke and Noone, 1985;Warren and Clarke, 1990;Grenfell et al, 2002;Lee Taylor and Madronich, 2002;Jacobson, 2004;Flanner et al, 2007;Doherty et al, 2010;Reay et al, 2012;Ye et al, 2012;King, 2013, 2014). Field observations and modelling simulations have also shown that increases in dust deposition to snow lead to radiative forcing that affects the energy balance of snow (Woo and Dubreuil, 1985;Aoki et al, 1998;Painter et al, 2007Painter et al, , 2012Huang et al, 2011;Wang et al, 2013;Zhang et al, 2013;Zhao et al, 2014;Yasunari et al, 2014). However, although anthropogenic deposits in polar snow and ice have been well characterised, studies on the effects of natural mineral aerosol deposits are more scarce.…”
Section: L Lamare Et Al: Mineral Aerosol Deposits On Sea Icementioning
confidence: 99%
“…AOD measurements were collected in cloudfree conditions between 11:00 and 13:00 (Beijing local time) to prevent the effects of optical distortions due to large solar zenith angles. Then, the Moderate Resolution Imaging Spectroradiometer (MODIS) on the Aqua and Terra satellites was used to retrieve the AOD and fire spot datasets (Kaufman et al, 1997;Zhang et al, 2013b;Zhao et al, 2014). The retrieved MODIS AOD is reliable and accurate when applied to three visible channels over vegetated land and ocean surfaces Ichoku et al, 2002a;.…”
Section: Aerosol Optical Depth and Snow Albedo Measurementsmentioning
confidence: 99%
“…However, models did not capture these potential large sources of local dust in snowpack and may overestimate BC forcing processes (Painter et al, 2007(Painter et al, , 2010(Painter et al, , 2012. Recently, several seasonal snow collection campaigns were performed across northern China, the Himalayas, North America, Greenland and the Arctic (Cong et al, 2015;Dang and Hegg, 2014;Doherty et al, 2010Doherty et al, , 2014Huang et al, 2011;Xu et al, 2009Xu et al, , 2012Zhao et al, 2014). However, determining the effects of ILAPs on snow albedo reduction continues to be challenging (Huang et al, 2011;Wang et al, 2013aWang et al, , 2015Ye et al, 2012;Zhang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…CLM4 in global and region applications has been shown to be accurate in describing snow, soil and vegetation processes Jin and Miller, 2007;Zhao et al, 2014). CLM4 includes 5 layers for snow, 10 layers for soil and 1 layer for vegetation.…”
Section: Land Surface Schemesmentioning
confidence: 99%